Pengelolaan Database Jalan Kabupaten Dan Lingkungan di Kabupaten Bengkulu Tengah - Endri Agustomi (MAJALAH TEKNIK SIMES, 2019)
Abstract The aim of the study was to check and evaluate pavement data and road conditions with an earth-based information system. The research location is in the district of Central Bengkulu. Data on research subjects for district and environmental roads. The research method used was map data collection, pavements and conditions with a length of 50-100 meters each. The system is run by taking field data with GPS, Photos and Videos. For pavements and conditions using direct observation. To display the information system, a web-based geographic information system (GIS Web) is used. This is intended to facilitate access from all walks of life of the application user.